The relationship between the cholesterol-low density lipoprotein/cholesterol-high density lipoprotein ratio with the incidence of acute coronary syndrome at RSUD kota Bandung in 2019-2022 - Feranika Feranika; Jihan Saskia Nursyabani; Primal Sudjana (Jurnal EduHealth, 2024)
The purpose of this study was to understand K-LDL levels with the incidence of acute coronary syndrome (ACS) in patients at the RSUD Kota Bandung Regional General Hospital (RSUD). The method used is a descriptive analytical method through a cross sectional approach to observe the Correlation of K-LDL/K-HDL Ratio with ACS (Acute Coronary Syndrome) events. The results of this study show that there is a correlation between the K-LDL/K-HDL ratio and ACS events at RSUD Kota Bandung in 2019 – 2021, this result can be concluded because it obtained a p value = 0.045. First, the majority of ACS patients at RSUD Kota Bandung in 2019 – 2021 are men, 65.6% of the total patients. Second, as many as 70.8% of the total patients of this study were active smokers. Third, the type of SKA that dominated in this study patient was APTS with 63.5% of the total respondents. Fourth, the average age of patients in these patients was 55.70 years. Fifth, the average ratio of LDL / HDL to ACS sufferers at RSUD Kota Bandung in 2019-2022 is 3,271. Sixth, the maximum and minimum values of LDL/HDL ratio in ACS patients at RSUD Kota Bandung in 2019 - 2022 are 7.037 and 0.215.